Nepotismo, clientelismo y fidelidad. De Floridablanca a Godoy (1789-1798) - Andújar Castillo, Francisco (Cuadernos de Historia Moderna, 2009)
During the reign of Carlos IV, and especially during the period of time in which the power was in Godoy’s hands, arbitrary actions in political decisions caused uncertainty among the main social actors of the monarchy. The King’s absolute power was transferred to other places where the major figures were the Prime Ministers. They benefited their relatives and customers and had a great influence upon the main monarchy institutions. They also used an exceptional executive way to appoint the king’s officers, which was based on nepotism and arbitrariness. This meant a change in the monarchy’s traditional order. Godoy got an extraordinary power, he looked for his own profit and had a big number of political customers who let him perpetuate his power. In order to achieve it, he controlled the main offices of Justice, Army, and Treasury.